Bear bile: dilemma of traditional medicinal use and animal protection - Nagamatsu Tadashi; Tsao Sai-Wah; Ng Kwan-Ming; Wang Ning; Siu Kayu; Feng Yibin; Tong Yao (BMC, 2009)
Abstract Bear bile has been used in Traditional Chinese Medicine (TCM) for thousands of years. Modern investigations showed that it has a wide range of pharmacological actions with little toxicological side effect and the pure compounds have been used for curing hepatic and biliary disorders for decades. However, extensive consumption of bear bile made bears endangered species. In the 1980's, bear farming was established in China to extract bear bile from living bears with "Free-dripping Fistula Technique". Bear farming is extremely inhumane and many bears died of illness such as chronic infections and liver cancer. Efforts are now given by non-governmental organizations, mass media and Chinese government to end bear farming ultimately. At the same time, systematic research has to be done to find an alternative for bear bile. In this review, we focused on the literature, laboratory and clinical results related to bear bile and its substitutes or alternative in English and Chinese databases. We examined the substitutes or alternative of bear bile from three aspects: pure compounds derived from bear bile, biles from other animals and herbs from TCM. We then discussed the strategy for stopping the trading of bear bile and issues of bear bile related to potential alternative candidates, existing problems in alternative research and work to be done in the future.